Answer:
The answer to your question is below
Explanation:
First system
2x - 2y = 12
-2x - 3y = -22
0 - 5y = -10
y = -10 / -5
y = 2
Solution (x , 2)
Second system
2x - 6y = 10
-2( x + 8y = 5)
2x - 6y = 10
-2x - 8y = -10
0 -14y = 0
y = 0 / -14
y = 0
2x - 6(0) = 10
2x = 10
x = 10/2
x = 5
Solution (5, y)
Third system
4(3x - y = - 5)
x + 4y = 7
12x - 4y = -20
x + 4y = 7
13x + 0y = -13
x = -13/13
x = -1
-1 -+ 4y = 7
4y = 7 + 1
4y = 8
y = 8/4
y = 2
Solution (x, 2)
Forth system
x - y = 2
2x + y = 13
3x = 15
x = 15/3
x = 5
Solution (5, y)